PERENCANAAN PENGELOLAAN SAMPAH TERPADU DI KECAMATAN KOTA KABUPATEN KUDUS - Tri Kustianto WW (Jurnal Teknik Lingkungan, 2012)
Management paradigm of solid waste with collection,  transportation and disposal system is time to replace with new paradigm. The compact solid waste management system is approximation system which reasonable as solution of solid waste problem. The integrated solid waste management is a systematic activity, completely, and connected overwhelm subtraction and solid waste handled (Act number 18 about Solid Waste Management, 2008). Solid waste management in Kota district there is at the moment to lean still at long pattern, that is solid waste at gather from the source, transpot to temporary receiver at residence, and discard to final disposal at residence. Solid waste which produced when not handled with well will to cause environment pollution, disturb beauty and dangered peple healty. The concept of compact solid waste management execute with doing maximaly solid waste reduction with solid waste manner in the nearest location of solid waste source, with approximation of law an regulation aspect, organization and institution aspect, operational technic aspect, expenditured and retribution aspect, also the society active people aspect.